"Are My Songs Literature?": A Postmodern Appraisal of Bob Dylan's American Popular Music Culture - Marwa Essam Eldin Alkhayat (Humaniora, 2018)
The current study is a postmodern appraisal of Bob Dylan’s artistic career and vocal gestures to examine the way melody in popular music works in relation to speech and singing, the grand and the ordinary. It historicizes Bob Dylan’s protest music of the 1960s within the paradigm of folk music culture. Dylan’s music is full of riffs, blues sequences, and pentatonic melodies—all heavily part and parcel of blues, folk, gospel, and country music. It is the music that dwells on the pleasures of repetition, of circularity, and of the recurring familiar tune integrated within Dylanesque poetics of rhyme delivered with his idiosyncratic, deep and intense range of voices. Dylan is the official son of the legacies of social, communal, and ritual music-making that mirrors contemporary pop and rock back to folk and blues, street-sung broadsides and work songs, the melodies of medieval troubadours, and the blessed rhythms of Christianity and Judaism. The study is an attempt to illustrate how musicology and ethnomusicology in particular can contribute to understanding Dylan as a ‘performing artist’ within the postmodern paradigm. Thus, the study seeks to establish Dylan as a phenomenal, prolific postmodernist artist, as well as an anarchist. The power and originality of Dylan’s music constitute a prima facie case that his performances should be considered postmodernist art.